A resilience-based approach for water resources management over a typical agricultural region in Northwest China under water-energy-food nexus. (November 2022) - Shen, Qianxi; Niu, Jun; Liu, Qi; Liao, Dehai; Du, Taisheng
Graphical abstract: Highlights: An evaluation system for water resources resilience was constructed and the driver was optimized. The input–output factors of farmland WEF system were considered in the optimization. The combination of film mulching and drip irrigation is found most effective in Zhangye City. WEF-based field management has great potential for saving water and increasing production. Abstract: Agriculture in the arid regions must take effective measures to cope with the constant challenges brought by climate warming and possible resource attenuation. As a typical agriculture region in Northwest China, the water resources resilience has been under varying degrees of pressure over the past two decades. To mitigate the stress of water resources, this study explored the optimal arrangement of agronomic and water-saving measures in farmland system under water-energy-food nexus. The finer simulations with reflecting the spatial heterogeneity was realized by employing G-AquaCrop model. Both water resources resilience evaluation model and the water-energy-food nexus coupling coordination evaluation model were constructed for the farmland system in the arid region. The results show that the combination of plastic film mulching and drip irrigation measures, among nine scenario sets of the different agronomic and water-saving measures, can be largely implemented in the Gaotai, Linze, Ganzhou and Minle Counties in Zhangye, which are mainly distributed in the lower reaches of the Heihe River basin in Northwest China. Alternative diversified management could be adopted elsewhere in the basin. The measures obtained have the merit of addressing the challenges of future climate change, especially for the agricultural regions in water-shortage area.